Ben Cao Gang Mu. Volume I, Part A, Introduction, History, Pharmacology, Diseases and Suitable Pharmaceutical Drugs I - Li, Shizhen (Berkeley : University of California Press, 2024)
Volume I is divided into two parts. Part A of volume 1 in the Ben cao gang mu series offers a translation of chapters 1 and 2 and portions of chapter 3. Chapters 1 and 2 are devoted to introducing the history of materia medica. Chapter 3 is devoted to pharmaceutical drugs for diseases. Chapter 3 is continued, along with chapter 4, in part B of volume I. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of.
Description based on online resource; title from digital title page (viewed on February 22, 2024).
JSTOR
Keywords: Medicine, Chinese -- Early works to 1800.; Materia medica -- China -- Early works to 1800.; Médecine chinoise -- Ouvrages avant 1800.; Matière médicale -- Chine -- Ouvrages avant 1800.; MEDICAL / Acupuncture; Materia medica; Medicine, Chinese; Drugs, Chinese -- Herbal; China; Early works